Full‐Polarization 3D Metasurface Cloak with Preserved Amplitude and Phase. Issue 32 (24th May 2016) - Yang, Yihao; Jing, Liqiao; Zheng, Bin; Hao, Ran; Yin, Wenyan; Li, Erping; Soukoulis, Costas M.; Chen, Hongsheng
Abstract : A full‐polarization arbitrary‐shaped 3D metasurface cloak with preserved amplitude and phase in microwave frequencies is experimentally demonstrated. By taking the unique feature of metasurfaces, it is shown that the cloak can completely restore the polarization, amplitude, and phase of light for full polarization as if light was incident on a flat mirror.